Evaluation of the Outcome Questionnaire-45.2 with a Mexican-American Population. Issue 1 (1st January 2017) - Ikonomopoulos, James; Lenz, A. Stephen; Guardiola, Rebekah; Aguilar, Alma
Abstract : We reported the evaluation of the Outcome Questionnaire 45.2 (OQ 45.2; Lambert et al., 1996) with a Mexican-American population for use in research and practice settings. Participants were 186 women and 80 men from South Texas and Mexican-American border locations. The procedure used to examine the psychometric properties of the OQ-45.2 assessment is described. The final analysis revealed a modest fit of the data for each of the hypothesized measurement models of the symptom distress, interpersonal relations, and social role subscales which have useful implications for treatment planning, evaluating outcomes, and developing programs. Counseling practice and future research implications are discussed.